Elevated Midtrimester Triglycerides as a Biomarker for Postpartum Hyperglycemia in Gestational Diabetes. (24th April 2020) - Lai, Mengyu; Fang, Fang; Ma, Yuhang; Yang, Jiaying; Huang, Jingjing; Li, Na; Kang, Mei; Xu, Xianming; Zhang, Jiarong; Wang, Yufan; Peng, Yongde
Abstract : Background . Whether elevated triglyceride (TG) levels during pregnancy were a biomarker for postpartum abnormal glucose metabolism (AGM) in women with previous gestational diabetes mellitus (GDM) remained unknown. The aim of this study was to investigate the association between TG levels during the second trimester and postpartum AGM in GDM women. Methods . This was a retrospective cohort study including 513 GDM women. A 75 g oral glucose tolerance test (OGTT) was performed, and lipid levels were determined during pregnancy and the postpartum period. GDM patients were categorized into tertiles according to their TG levels at 24–28 weeks of gestation (TG < 2.14   mmol / L, TG: 2.14–2.89 mmol/L, and TG > 2.89   mmol / L ). A logistic regression model was used to calculate the odds ratios (ORs) and 95% confidence intervals (CIs). Results . During pregnancy, women in the high TG tertile showed higher HbA1c levels (5.47 ± 0.58 % versus 5.28 ± 0.49 %, p = 0.006 ), higher total cholesterol (TC) levels (5.85 ± 1.23   mmol / L versus 5.15 ± 0.97   mmol / L, p = 0.026 ), and higher HOMA-IR (2.36 (1.62-3.45) versus 1.49 (0.97-2.33), p < 0.001 ) than the participants in the low TG tertile. After delivery, the prevalence rates of AGM based on above tertiles of TG levels during pregnancy were 26.90%, 33.33%, and 43.27%, respectively (p = 0.006 ). High TG tertile during the second trimester was associated with the presence of postpartum AGM (adjusted OR: 2.001, 95% CI: 1.054-3.800, p = 0.034 ). Conclusions . The elevated midtrimester TG levels were not only accompanied by higher glucose and lipid levels and more severe insulin resistance at the time of the measurement but were a biomarker for postpartum AGM as well.